Altered intrinsic functional brain architecture in female patients with bulimia nervosa - Wang, Li (J Psychiatry Neurosci, 2017)
BACKGROUND: Bulimia nervosa is a severe psychiatric syndrome with uncertain pathogenesis. Neural systems involved in sensorimotor and visual processing, reward and impulsive control may contribute to the binge eating and purging behaviours characterizing bulimia nervosa. However, little is known about the alterations of functional organization of whole brain networks in individuals with this disorder. METHODS: We used resting-state functional MRI and graph theory to characterize functional brain networks of unmedicated women with bulimia nervosa and healthy women. RESULTS: We included 44 unmedicated women with bulimia nervosa and 44 healthy women in our analyses. Women with bulimia nervosa showed increased clustering coefficient and path length compared with control women. The nodal strength in patients with the disorder was higher in the sensorimotor and visual regions as well as the precuneus, but lower in several subcortical regions, such as the hippocampus, parahippocampal gyrus and orbitofrontal cortex. Patients also showed hyperconnectivity primarily involving sensorimotor and unimodal visual association regions, but hypoconnectivity involving subcortical (striatum, thalamus), limbic (amygdala, hippocampus) and paralimbic (orbitofrontal cortex, parahippocampal gyrus) regions. The topological aberrations correlated significantly with scores of bulimia and drive for thinness and with body mass index. LIMITATIONS: We reruited patients with only acute bulimia nervosa, so it is unclear whether the topological abnormalities comprise vulnerability markers for the disorder developing or the changes associated with illness state. CONCLUSION: Our findings show altered intrinsic functional brain architecture, specifically abnormal global and local efficiency, as well as nodal- and network-level connectivity across sensorimotor, visual, subcortical and limbic systems in women with bulimia nervosa, suggesting that it is a disorder of dysfunctional integration among large-scale distributed brain regions. These abnormalities contribute to more comprehensive understanding of the neural mechanism underlying pathological eating and body perception in women with bulimia nervosa.